Construction of Promethazine Hydrochloride Selective Electrodes in A Pvc Matrix Membrane - Al-Saidi, Khaleda H; Ahmed, Zainab W (Al-Nahrain Journal of Science, 2011)
Promethazine hydrochloride selective electrodes were constructed based on promethazine-Molybdophosphoric acid ion pair. Promethazine hydrochloride electrodes (1, 2, 3, 4 and 5) using these plasticizers Di-butyl phthalate (DBPH); Di-octyl phthalate (DOP); Di-butyl phosphate (DBP); Tri-butyl phosphate (TBP); ortho-nitro phenyl octyl ether (ONPOE) in PVC matrix respectively. These electrodes give slopes (57.27, 54.08, 49.79, 46.76 and 44.52 mV/decade) and give linear ranges from (1×10-5-1×10-1, 1×10-4-1×10-1, 1×10-5- 1×10-1, 5×10-4-1×10-1 and 1×10-4-1×10-1 M) respectively. The best detection limit was 6×10−6 M for the electrode based on DBPH. The measurement interferences in the presence of (Na+, K+, Mn+2, Cu+2, Ca+2, Fe+3, Al+3, Paracetamol, sucrose and Galaten) were studied using separate and mixed methods for selectivity coefficient determination. The pH and life time of the electrodes were also studied. The results were compared with UV-spectrophotometer technique by using F-test.